2015
DOI: 10.4103/0970-9371.155226
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic challenges in cytology of mucoepidermoid carcinoma: Report of 6 cases with histopathological correlation

Abstract: Background:Mucoepidermoid carcinoma (MEC) is a malignant salivary gland neoplasm with extreme morphologic heterogeneity and hence rendering a definitive fine needle aspiration cytology (FNAC) diagnosis of this neoplasm is really challenging. The present study was undertaken to elucidate the cytological features of MEC and explore the diagnostic accuracy and pitfalls by comparing with subsequent histopathology.Materials and Methods:The present study was conducted over a period of 2 years wherein we obtained six… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 12 publications
1
29
0
Order By: Relevance
“…Several authors have reported difficulties in the diagnosis of high grade MEC. 6,11,14,15 Table 4 showed FNAC cases categorized as AUS and SUMP. The AUS category at our institution showed an overall frequency of 5.3%, in agreement with the MSRSGC recommendation to keep them as <10% of all salivary gland diagnoses.…”
Section: Illustrative Casesmentioning
confidence: 99%
“…Several authors have reported difficulties in the diagnosis of high grade MEC. 6,11,14,15 Table 4 showed FNAC cases categorized as AUS and SUMP. The AUS category at our institution showed an overall frequency of 5.3%, in agreement with the MSRSGC recommendation to keep them as <10% of all salivary gland diagnoses.…”
Section: Illustrative Casesmentioning
confidence: 99%
“…Because of the mucin secretion, FNAs are often not very cellular, and sometimes glandular goblet cells are lacking. Differential diagnoses include benign cysts (especially in the submandibular gland) or mucin‐rich variants of salivary duct carcinoma . Indeed, the oncocytic variant of mucoepidermoid carcinoma may be impossible to differentiate from other oncocytic tumours.…”
Section: Discussionmentioning
confidence: 99%
“…However, these data are variable according to different publications and are dependent upon the learning curve of the observer. Among the main pitfalls of FNA, mucoepidermoid carcinoma may be missed or misinterpreted as pleomorphic adenoma or squamous cell carcinoma . Adenoid cystic carcinoma may share features with those observed in pleomorphic adenoma and mammary analogue secretory carcinoma (MASC) or may be misinterpreted as acinic cell carcinoma or mucoepidermoid carcinoma …”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, PA, commonly followed by chronic sialadenitis and WT, may mimic low-grade MEC [31]. In a study of 6 cases of MEC by Joseph et al [36], the correct diagnosis was rendered only in 2 cases. The remaining cases were misdiagnosed as neoplastic with cystic degeneration (n = 2) and PA (n = 2).…”
Section: Discussionmentioning
confidence: 99%